Effect of pointed and diffused air injection on premixed flame confined in a Rijke tube. Issue 1 (31st December 2016) - Deshmukh, Nilaj N.; Sharma, S.D.
Abstract: The coupling between pressure fluctuations and unsteady heat release in a combustion systems results in acoustic oscillations inside the combustion system. These acoustic oscillations, when grow sufficiently, may cause serious structural damage thereby reducing the lifespan of jet engines, gas turbines, and industrial burners. The aim of the first part of study is to define acoustically stable and unstable regions. The second part is focused on studying the effect of change in pressure field near the flame on the amplitude and frequency of the oscillations of instability. This study is carried out for three-burner positions and equivalence ratio of 0.7 by varying heat supply and total flow rate. The results show two acoustically unstable regions for 0.1 and 0.2 burner positions and only one acoustically unstable region for 0.25 burner position. The effect of pointed injection and diffused injection over a premixed flame on the sound pressure level was studied. The results show for burner position of x /L = 0.2 there is 25 dB suppression is possible using pointed injection at higher total flow rate. The experiment of diffused injection shows sound amplification more than 12 dB was observed.